3D Progressive Education Environment for S-BPM - Weichhart, G.; Pirker, J.; Guetl, Christian; Stary, C. (Springer International Publishing, 2014)
The work described in this paper combines our existing work on virtual 3D worlds and progressive education, applying it in order to support tbe education of S-BPM. The application of the approaches results in a demonstrator developed for S-BPM-One 2014 conference. The paper presents the underlying theory and motivation for the demonstrator. An outlook with respect to what is visible in the described e-learning 3D World is given.